Absence of bovine leukemia virus in the buffy coats of breast cancer cases from Alabama, USA. (December 2021) - Adekanmbi, Folasade; McNeely, Isaac; Omeler, Sophonie; Kalalah, Anwar; Poudel, Anil; Merner, Nancy; Wang, Chengming
Abstract: Breast cancer is reported as one of the most common and deadly cancers among females. Recent findings have suggested that bovine leukemia virus (BLV), a highly prevalent bovine virus worldwide, might be linked to human breast cancer. However, the involvement of BLV as a risk factor for breast cancer remains controversial. In this study, BLV FRET-PCR was carried out on 238 blood-derived DNA samples from breast cancer patients from the Alabama Hereditary Cancer Cohort. In addition, randomly selected samples (n = 20) were evaluated by WGS for the presence of BLV genome. No BLV proviral DNA was detected in any of 238 samples assayed by FRET-qPCR in this study. Similarly, the WGS analysis did not detect the presence of the BLV genome in the DNA of the buffy coats from 20 randomly selected patients with breast cancer. This study did not support the findings of suggesting an association between BLV and breast cancer. Notably, nearly all the studies using in situ PCR and immunohistochemistry demonstrated positive associations while other studies using whole-genome sequencing and other methods failed to identify the BLV association with breast cancer. Further studies including all reported BLV detection techniques/methods on the same breast cancer sample sets would appear to be the most likely way of resolving the current contradictory evidence. Highlight: FRET-PCR did not detect BLV in any of 238 blood samples from breast cancer patients. WGS did not reveal BLV in the DNA of the buffy coats from 20 breast cancer patients. This study did not support findings of an association between BLV and breast cancer.